1995
DOI: 10.1089/hum.1995.6.3-297
|View full text |Cite
|
Sign up to set email alerts
|

Polyoma Virus Pseudocapsids as Efficient Carriers of Heterologous DNA into Mammalian Cells

Abstract: Polyoma virus VP1 pseudocapsids, generated from a recombinant baculovirus, have been successfully used to transfer exogenous DNA stably into rodent (rat-2) cells. To evaluate the efficiency and biological usefulness of this route for introducing heterologous DNA into cells, the gene for a transforming deletion mutant of the middle T antigen of polyoma virus, dl8 MT, was used initially. Whereas the amount of DNA packaged together with pseudocapsids was found to be variable (2-30%), even at low efficiency its tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
91
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 21 publications
3
91
0
Order By: Relevance
“…Moreover, according to this hypothesis, branched SA-containing molecules, also designated by Bauer et al (1999) as pseudoreceptors, could represent glycoproteins that allow MPyV cell attachment but not secondary post-attachment interactions with the protein moiety required for virus internalization. Further investigation in this direction is required to develop tissue-restricted MPyV VLP-based vectors for gene therapy (Forstovà et al, 1995;Soeda et al, 1998;Krauzewicz & Griffin, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, according to this hypothesis, branched SA-containing molecules, also designated by Bauer et al (1999) as pseudoreceptors, could represent glycoproteins that allow MPyV cell attachment but not secondary post-attachment interactions with the protein moiety required for virus internalization. Further investigation in this direction is required to develop tissue-restricted MPyV VLP-based vectors for gene therapy (Forstovà et al, 1995;Soeda et al, 1998;Krauzewicz & Griffin, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Initial transfection lysates were used to subsequently infect cells in order to increase baculovirus titres. Production and purification of VLPs were by CsCl and sucrose gradients, as described previously (Forstovà et al, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Murine polyomavirus VP1 is able to self-assemble into a capsid-like particle when expressed in insect cells (Forstova et al, 1993 ;Gillock et al, 1997 ;Montross et al, 1991). Forstova et al (1995) demonstrated that murine polyomavirus VP1 pseudocapsids generated from a recombinant baculovirus are able to transfer heterologous DNA efficiently into mammalian cells. More recently, SV40 pseudovirions self-assembled in insect cells have also been shown to be able to introduce foreign genes into mammalian cells (Sandalon et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Procedures for packaging exogenous DNA into pseudocapsid particles were described by Forstova et al (1995). Briefly, 40 µg pseudocapsid protein was mixed with 3 µg pEGFP-C1 plasmid DNA (Clontech) in 150 mM NaCl, 10 mM Tris-HCl, pH 7n4, 0n01 mM CaCl # .…”
Section: Methodsmentioning
confidence: 99%
“…While polylysine-ligand conjugates for tar-5.5V exhibit the ability to package DNA into transfectiongeting surface receptors of the host cell in complex with active protein-DNA complexes. These protein fractions DNA via the endocytotic pathway 3 or viral capsid prowere obtained by extraction of nuclei with 5% perchloric teins 4 have been used successfully in gene transfer, acid and subsequent gradual acetone precipitation of nuclear proteins have received little attention. The nonhithese extracts.…”
mentioning
confidence: 99%